Past, present and future of surgical simulation and perspective of a developing country: a narrative review - Mohammad Sohail Asghar; Balakh Sher Zaman; Aima Zahid (Journal of the Pakistan Medical Association, 2022)
Healthcare systems around the globe have been revolutionized in the last few decades and it has resulted in a greater need and demand for surgical education outside the operation theaters. Surgical education through simulations started around 2500 years ago where they were first used in the planning of the unique and innovative surgeries while ensuring the safety of the subjects. Currently simulations include animal models, cadaveric models, bench top models, complex robotic models. In a program involving surgical simulators, four requirements will be followed to optimize their effectiveness, including mandatory involvement, skill-based instruction, standardized training plan and overtraining. We can make a reasonable estimation that the future is technology. The speed with which we anticipate the fusion of these Virtual Reality and Robotics based Simulation technology with medical educations and practices largely depends on affordability and economics of these tools. Continuous...